Komunikasi, Komitmen Organisasi dan Kompetensi terhadap Kinerja Pegawai PNS Dishub - Sage, Nur Hasmah; Muslimin, Ulyana; Alimuddin, Firman; Rifani, Riza Amalia (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to determine how much influence communication, organizational commitment and competence have on the performance of civil servants at the Department of Transportation. The analytical method used is descriptive quantitative, using primary data sourced from the results of the questionnaires that have been answered by the respondents. The tests used include validity test, reliability test, descriptive analysis, multiple linear regression analysis and t test (partial), F test (simultaneous), R2 test (coefficient of determination). The results showed that: 1. Communication (X1) test results showed the value of t = (3.264) with a significance value of 0.002 <0.05. This value proves that communication (X1) has a significant effect on employee performance. 2. Organizational Commitment (X2) The test results show the value of t = (0.344) with a significance value of 0.733> 0.05. This value proves that organizational commitment (X2) has no significant effect on employee performance. 3. Competence (X3) test results show the value of t = (0.261) with a significance value of 0.796> 0.05. This value proves that competence (X3) has no effect and is not significant on employee performance